2014
DOI: 10.1097/ruq.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Not All Radiopaque Foreign Bodies Shadow on Ultrasound

Abstract: Foreign body ingestion is a common indication for imaging children. Ultrasound can be a useful adjunct to serial radiographs for evaluation of foreign bodies in the enteric tract. This case report describes a child who swallowed a single magnetic rock. Follow-up radiographs 4 days later could not determine progression of the foreign body beyond the stomach. Ultrasound was used to locate it, showing a structure with unexpected posterior reverberation artifact in the stomach. This was correlated with a similar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…We have shown that both Buckyball-type and button magnets are intrinsically highly echogenic and produce significant reverberation artifact due to their smooth and highly reflective surfaces. This is congruent with findings published in a 2014 study of magnets in the stomach [ 25 ]. Furthermore, ultrasound allows us to further evaluate the orientation of magnets in relation to the bowel loops.…”
Section: Discussionsupporting
confidence: 93%
“…We have shown that both Buckyball-type and button magnets are intrinsically highly echogenic and produce significant reverberation artifact due to their smooth and highly reflective surfaces. This is congruent with findings published in a 2014 study of magnets in the stomach [ 25 ]. Furthermore, ultrasound allows us to further evaluate the orientation of magnets in relation to the bowel loops.…”
Section: Discussionsupporting
confidence: 93%
“…This is because if the FB is completely surrounded by the mucosa, only gastric mucosa edema and purulent external pressure can be seen under the endoscope. Even with further ultrasound gastroscopy, not all radiopaque FBs produce shadows on ultrasound images [ 30 ]. On the other hand, patients often suffer from unspecific symptoms without a clear chief complaint of FB ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the relevance of this phenomenon from the public health perspective, it is often neglected (Gregori et al, 2011 ; Passali et al, 2015 ). Generally, studies in this field are retrospective, single-center, case series (Brown et al, 2014b ; Sahadan et al, 2011 ) or case studies (Chan et al, 2014 ; Nivatvongs et al, 2015 ), but a systematic collection of data on choking injuries is lacking. In this framework, one of the few examples of systematic data collection on FB injuries is represented by the Susy Safe registry (Gregori, 2006 ).…”
Section: Introductionmentioning
confidence: 99%